The effect of convergent action on reducing stunting prevalence in under-five children in Banggai District, Central Sulawesi, Indonesia - Aspar Abdul Gani; Veni Hadju; Akmal Novrian Syahruddin; Anang S. Otuluwa; Sukri Palutturi; Abdul Razak Thaha (Elsevier, 2021)
Objective: This study aimed to assess the amount of changes in prevalence of stunting after one-year convergence intervention. Methods: This was an evaluation study of national program that implemented in Banggai District beginning 2018. There were ten villages (n = 532) that included in the program based on severity of stunting prevalence. Data were analyzed using chi-square and independent t-test using SPSS. Result: After a year program, stunting reduced to 38.91% or 2.18% from the baseline (41.09%). The highest reduction was in at 0-5 mo (8.59%) and 6-11 mo (8.46%). There was no difference using height for age z-score in all ages (−1.64 ± 1.19 to −1.59 ± 1.38, p = 0.506). However, the reduction was significant at 0-11 months (−1.20 ± 1.23 to 0.78 ± 1.58, p = 0.020) but no in other age categories (p > 0.05). Conclusion: The convergence action for one year intervention reduced significantly stunting in 0-11 months of children but not in other age categories of under five children.